(untitled) (PANGEEA, 2025)
This paper discusses the heavy metals pollution, particularly lead (Pb), and evaluates its effects on health in polluted zones around Zlatna. It characterizes the pollution phenomena, sources of heavy metals, their distribution and metabolism within the human organism, and the toxicological implications including risk factors for long-term exposure. The study highlights absorption routes, tissue distribution, and potential screening approaches to identify high-risk individuals.